Perancangan Prototipe Miniatur Pembangkit Listrik Tenaga Air - Wasiran, Wasiran; Yudisworo, W. Djoko (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2025)
The prototype tool of the hydroelectric power plant is an engineering tool as a demonstration of a power plant that is moved by water. So the tool will be redesigned by researchers as a comparison of courses in mechanical engineering study programs, especially engineering thermodynamics courses. In the design of the tool will be designed using the solid work computer program. Then in the selection of design components that are used are easily obtained or within reach of purchasing the tool, namely the frame holder for the power plant using holo steel, a water pump using a 260 bit jet pump that uses 200 watts of electric power, electricity supply using an alternator that has 200 watts of electric power. The water-driven turbine is the process made using Pvc pipe which has a tilt angle on the blade of 30 o. turbine cover using acrylic material with a thick size of 10 mm, water reservoir using steel plate size 4 mm and lamp load that will be tested 100 watt capacity. At the capacity of this tool requires a cost of approximately Rp. 5,811,500,